64-multidetector CT anatomical assessment of the feline bronchial and pulmonary vascular structures. Issue 10 (October 2019) - Panopoulos, Ioannis; Auriemma, Edoardo; Specchi, Swan; Diana, Alessia; Pietra, Marco; Papastefanou, Anastasia; Zini, Eric; Cipone, Mario
Objectives: The aim of the study was to provide a detailed anatomical study of the feline bronchial and vascular structures by using CT angiography (CTA). Methods: Adult cats with no respiratory clinical signs were enrolled in a CTA protocol to provide an anatomical study of the thorax. The dimensions, number of branches and branching pattern (monopodial vs dichotomic) of both bronchial and pulmonary vascular structures were evaluated under positive inspiration apnoea. A linear generalised estimating equations analysis (Spearman's rho) was used to identify statistical correlation between tracheal diameter, age and body weight of the cats. Results: Fourteen cats met the inclusion criteria. The pulmonary arteries had larger diameters than the pulmonary veins, and the pulmonary veins had larger diameters than the bronchial structures. A higher number of segmental bronchial and pulmonary vascular branches was observed in the left caudal lung lobe than in the other lobes. The monopodial branching pattern of both bronchial and pulmonary vascular structures was predominant in all cats of our study (100%) in cranial, caudal and right middle lung lobes, while a dichotomic branching pattern of the bronchial and pulmonary vascular structures of the accessory lung lobe was seen in 13 cats (93%). Thirteen cats (93%) had three pulmonary vein ostia, and one cat (7%) also presented with an additional left intermediate pulmonary vein ostium. Variation in the number of segmental pulmonary vein branches was noted in the right caudal lung lobe. There was no statistical correlation between tracheal diameter, age and weight. Conclusions and relevance: Architecture of the feline bronchovascularr structures belongs to a mixed type of monopodial and dichotomic branching pattern. In cats, the pulmonary venous drainage system predominately presents three pulmonary vein ostia. Variations in the type of formation and the number of branches of the pulmonary venous drainage system were noted.